Increased Severity of Tuberculosis in Guinea Pigs with Type 2 Diabetes: A Model of Diabetes-Tuberculosis Comorbidity - Podell, Brendan K. (American Society for Investigative Pathology, 2014)
Impaired glucose tolerance and type 2 diabetes were induced in guinea pigs to model the emerging comorbidity of Mycobacterium tuberculosis infection in diabetic patients. Type 2 diabetes mellitus was induced by low-dose streptozotocin in guinea pigs rendered glucose intolerant by first feeding a high-fat, high-carbohydrate diet before M. tuberculosis exposure. M. tuberculosis infection of diabetic guinea pigs resulted in severe and rapidly progressive tuberculosis (TB) with a shortened survival interval, more severe pulmonary and extrapulmonary pathology, and a higher bacterial burden compared with glucose-intolerant and nondiabetic controls. Compared with nondiabetics, diabetic guinea pigs with TB had an exacerbated proinflammatory response with more severe granulocytic inflammation and higher gene expression for the cytokines/chemokines interferon-γ, IL-17A, IL-8, and IL-10 in the lung and for interferon-γ, tumor necrosis factor-α, IL-8, and monocyte chemoattractant protein-1 in the spleen. TB disease progression in guinea pigs with impaired glucose tolerance was similar to that of nondiabetic controls in the early stages of infection but was more severe by day 90. The guinea pig model of type 2 diabetes–TB comorbidity mimics important features of the naturally occurring disease in humans. This model will be beneficial in understanding the complex pathogenesis of TB in diabetic patients and to test new strategies to improve TB and diabetes control when the two diseases occur together.